Aproximación de plan de exportación de pitahaya amarilla de origen colombiano a Japón (2021)
For many decades Japan has been one of the leading countries in the world economy and trade and for any nation that wishes to boost its economic development, this country should be a strategic objective due to the size of the market and the high purchasing power of its population. In addition to being a mandatory and very important reference in terms of technological development, quality and innovation. There are many lessons of success and at the same time many opportunities that Japan offers and that Colombia can take advantage of with an adequate strategy. In this context, the efforts of our country to internationalize its economy, to reach new markets and diversify the exportable offer must necessarily have this Asian power as a clear objective to successfully enter the large Asian market and to strengthen the regional initiative of the Pacific Alliance.